Current status of digital dental surgery - Ivkovic, Rastko; Miladinovic, Emil (PONS - medicinski časopis, 2019)
At the end of the 20th century, the introduction of computer technology into oral surgery created great expectations. In almost two decades of the 21st century, computer technologies entered deep into the pores of oral surgery and we witnessed their full expansion there. Computer technologies extend across different areas and offer support to oral surgeons in patient management. This paper represents a review of most recent advances of computer-assisted dentistry in the domain of oral surgery. The paper is intended to inform the reader about the advantages and shortcomings of computer-assisted oral surgery in both research and clinical practice.